The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/ijms21062041
|View full text |Cite
|
Sign up to set email alerts
|

UbcH10 a Major Actor in Cancerogenesis and a Potential Tool for Diagnosis and Therapy

Abstract: Malignant transformation is a multistep process in which several molecular entities become dysregulated and result in dysfunction in the regulation of cell proliferation. In past years, scientists have gradually dissected the pathways involved in the regulation of the cell cycle. The mitotic ubiquitin-conjugating enzymes UbcH10, has been extensively studied since its cloning and characterization and it has been identified as a constantly overexpressed factor in many types of cancer. In this paper, we have revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…The copyright holder for this preprint this version posted October 6, 2022. ; https://doi.org/10.1101/2022.10.04.510674 doi: bioRxiv preprint identified as a prognostic marker 30 and associated with cancer grade progression 31 and drug resistance 32 . Similar observations were made in colon, ovarian, and bladder cancers, among other types of tumors [33][34][35][36] . Interestingly, UBE2C was associated with BM in a recent publication, where single-cell RNA sequencing of BM from multiple cancers led to the identification of two subgroups, being UBE2C one of the signature genes in the proliferative group 25 .…”
Section: Discussionsupporting
confidence: 83%
“…The copyright holder for this preprint this version posted October 6, 2022. ; https://doi.org/10.1101/2022.10.04.510674 doi: bioRxiv preprint identified as a prognostic marker 30 and associated with cancer grade progression 31 and drug resistance 32 . Similar observations were made in colon, ovarian, and bladder cancers, among other types of tumors [33][34][35][36] . Interestingly, UBE2C was associated with BM in a recent publication, where single-cell RNA sequencing of BM from multiple cancers led to the identification of two subgroups, being UBE2C one of the signature genes in the proliferative group 25 .…”
Section: Discussionsupporting
confidence: 83%
“…The normal progress of this process is related to successful completion of the cell cycle and signal transduction. 28 Our results showed that UBE2C is overexpressed in NSCLC tissues (57.1%) and is rarely expressed in normal tissues (15.6%). We found that UBE2C overexpression was associated with a larger tumor volume, LNM, and later clinical stage, suggesting that it might be involved in the growth and metastasis of NSCLC.…”
Section: Discussionmentioning
confidence: 54%
“…Their contribution to the ubiquitination of the APC/c RING E3 complex and to cell cycle progression has been extensively studied in breast cancer [ 52 ]. Both UBE2S and UBE2C have been proposed as therapeutic targets in various cancers including EOC [ 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%